Interleukin (IL)-21 in Inflammation and Immunity During Parasitic Diseases - Solaymani-Mohammadi, Shahram; Eckmann, Lars; Singer, Steven M. (Frontiers in Cellular and Infection Microbiology, 2019)
Parasitic diseases cause significant morbidity and mortality in the developing and underdeveloped countries. No efficacious vaccines are available against most parasitic diseases and there is a critical need for developing novel vaccine strategies for care. IL-21 is a pleiotropic cytokine whose functions in protection and immunopathology during parasitic diseases have been explored in limited ways. IL-21 and its cognate receptor, IL-21R, are highly expressed in parasitized organs of infected humans as well in murine models of the human parasitic diseases. Prior studies have indicated the ability of the IL-21/IL-21R signaling axis to regulate the effector functions (e.g., cytokine production) of T cell subsets by enhancing the expression of T-bet and STAT4 in human T cells, resulting in an augmented production of IFN-γ. Mice deficient for either IL-21 (Il21−/−) or IL-21R (Il21r−/−) showed significantly reduced inflammatory responses following parasitic infections as compared with their WT counterparts. Targeting the IL-21/IL-21R signaling axis may provide a novel approach for the development of new therapeutic agents for the prevention of parasite-induced immunopathology and tissue destruction.